Solid-state battery positive electrode and preparation method thereof
The solid-state battery electrode's gradient ionic conductivity profile, achieved through layered sub-layers with varying polymer additive molecular weights, addresses the conductivity limitations in solid-state batteries, improving rate performance and capacity by optimizing active material distribution and ion transport.
Patent Information
- Application Number
- CN202311270587.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Solid-state battery electrodes face low ionic conductivity due to particle separation and poor connection between polymer electrolytes, limiting battery performance to low charge-discharge rates and capacity, especially as electrode thickness increases.
A solid-state battery electrode design featuring a gradient ionic conductivity profile achieved by layering active sub-layers with varying polymer additive molecular weights, optimizing the distribution of active materials, conductive agents, and lithium salts to enhance ion transport and reduce polarization.
This design improves the utilization of active materials, balances charge distribution, and enhances lithium ion transmission, thereby increasing battery rate performance and capacity while minimizing polarization.
Smart Images

Figure CN119725375A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the technical field of battery positive electrode preparation, and in particular to a solid-state battery positive electrode and a preparation method thereof. Background Art
[0002] Polymer electrolytes have the advantages of being non-flammable, easy to process, and having a wide range of raw material sources, and have been widely used in the field of solid-state batteries. However, the ionic conductivity of polymer electrolytes themselves is relatively low. Due to particle barriers, the connection between polymers is not tight, resulting in low ionic conductivity of the composite positive electrode, which in turn means that the battery can only be charged and discharged under low rate conditions. In addition, the fluidity of polymer electrolytes is much lower than that of liquid electrolytes, resulting in significant differences in the transmission of lithium ions in the composite positive electrode. The thicker the composite positive electrode, the lower the ionic conductivity close to the current collector side, which seriously affects the rate performance and capacity of the battery.
[0003] Currently, there are two main methods to improve the ionic conductivity of positive electrode materials: one is to modify the positive electrode material by coating the surface of the active material with a material with high ionic conductivity or by doping doping atoms into the active material. However, the coating and doping process is complicated, and the coating and doping amounts are uncontrollable, which will lead to obvious differences in local ionic conductivity. The second is to optimize the formula by adjusting the composition and proportion of the positive electrode active material, solid electrolyte and conductive agent, thereby improving the diffusion mode of lithium ions inside it. However, this method has limited effect on the improvement of ionic conductivity. Summary of the invention
[0004] In view of this, the present application provides a solid-state battery positive electrode, which includes a current collector and a positive electrode active layer arranged on the current collector, the positive electrode active layer includes a positive electrode active material, a polymer additive and a conductive agent, and the positive electrode active layer includes at least two stacked active sublayers, and in any two adjacent active sublayers, the weight average molecular weight of the polymer additive in the active sublayer away from the current collector is greater than the weight average molecular weight of the polymer additive in the active sublayer close to the current collector. The solid-state battery positive electrode has a gradient ion conductivity in the thickness direction, which can improve the utilization rate of the active material on the current collector side of the positive electrode and increase the capacity, while balancing the charge in the thickness direction of the pole piece and reducing polarization, optimizing the lithium ion transmission path and improving the battery rate performance. The present application also provides a method for preparing the solid-state battery positive electrode.
[0005] In a first aspect, the present application provides a solid-state battery positive electrode, which includes a current collector and a positive electrode active layer arranged on the current collector, the positive electrode active layer includes a positive electrode active material, a polymer additive and a conductive agent, and the polymer additive includes one or more of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polytetrafluoroethylene, polyacrylonitrile, polypropylene carbonate, polyethylene oxide and ethylene oxide-propylene oxide copolymer; the positive electrode active layer includes at least two stacked active sublayers, and in any two adjacent active sublayers, the weight average molecular weight of the polymer additive in the active sublayer away from the current collector is greater than the weight average molecular weight of the polymer additive in the active sublayer close to the current collector.
[0006] In the embodiment of the present application, the thickness of the current collector is 8 μm-20 μm, and the thickness of the active sublayer is 50 μm-250 μm.
[0007] In the embodiment of the present application, the weight average molecular weight of the polymer additive is 10000 g / mol-1000000 g / mol.
[0008] In an embodiment of the present application, in any two adjacent active sublayers, the weight average molecular weight of the polymer additive in the active sublayer away from the current collector is 100,000 g / mol-600,000 g / mol greater than the weight average molecular weight of the polymer additive in the active sublayer close to the current collector.
[0009] In the embodiment of the present application, the mass ratio of the positive electrode active material, the polymer additive and the conductive agent in the positive electrode active layer is (50-90): (6-20): (1-10).
[0010] In the embodiment of the present application, the positive electrode active material includes lithium cobalt oxide, lithium nickel oxide, lithium iron phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium nickel phosphate, lithium manganese oxide, LiNi x A (1-x) O2 and LiNi m E n M (1-m-n) O2, wherein A is selected from any one of Co and Mn, E and M are selected from any one of Co, Al and Mn, and E and M are different, 0 <x<1,0<m<1,0<n<1;、
[0011] In an embodiment of the present application, the conductive agent includes one or more of acetylene black, Super P, Super S, graphene, carbon fiber, carbon nanotube and Ketjen black.
[0012] In the embodiment of the present application, the positive electrode active layer further includes a lithium salt and / or a plasticizer.
[0013] In an embodiment of the present application, the lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium dioxalatoborate, lithium difluorooxalatoborate and lithium tetrafluorooxalatophosphate.
[0014] In the embodiment of the present application, the plasticizer includes one or more of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol methyl ethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, 1,4-dioxane, succinonitrile and polyethylene glycol dimethyl ether having a weight average molecular weight of less than 1000.
[0015] The second aspect of the present application provides a method for preparing a positive electrode of a solid-state battery, comprising:
[0016] Providing at least two composite positive electrode slurries, each of the composite positive electrode slurries comprises a positive electrode active material, a polymer additive and a conductive agent, and the polymer additives in the at least two composite positive electrode slurries have different weight average molecular weights;
[0017] By co-extrusion, the at least two composite positive electrode slurries are layered and coated on the surface of the current collector in the order of the weight average molecular weight of the polymer additives from low to high, so as to obtain a solid-state battery positive electrode precursor;
[0018] The solid-state battery positive electrode precursor is dried and rolled to obtain a solid-state battery positive electrode; the solid-state battery positive electrode includes a current collector and a positive electrode active layer arranged on the current collector, the positive electrode active layer includes at least two stacked active sublayers, and in any two adjacent active sublayers, the weight average molecular weight of the polymer additive in the active sublayer away from the current collector is greater than the weight average molecular weight of the polymer additive in the active sublayer close to the current collector.
[0019] The third aspect of the present application provides a solid-state battery, which includes a positive electrode, a negative electrode and a solid electrolyte located between the positive electrode and the negative electrode, and the positive electrode includes the solid-state battery positive electrode provided in the first aspect of the present application.
[0020] The fourth aspect of the present application provides an electrical device, which includes the solid-state battery provided by the third aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 A schematic diagram of the structure of a positive electrode of a solid-state battery provided in one embodiment of the present application;
[0022] Figure 2 A schematic diagram of the structure of a positive electrode of a solid-state battery provided in another embodiment of the present application;
[0023] Figure 3 A schematic diagram of the structure of a solid-state battery provided in an embodiment of the present application.
[0024] Description of Figure Numbers
[0025] 100 - positive electrode of solid-state battery; 101 - current collector; 102 - positive electrode active layer; 1021 - first active sublayer; 1022 - second active sublayer; 1023 - third active sublayer; 200 - solid-state battery; 201 - positive electrode; 202 - solid electrolyte; 203 - negative electrode. DETAILED DESCRIPTION
[0026] The present application is further described in detail below in conjunction with preferred embodiments, but the protection scope of the present application is not limited to the following specific embodiments.
[0027] In the present application, all professional terms have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present application.
[0028] Polymer electrolytes have the advantages of being non-flammable, easy to process, and having a wide range of raw material sources, and have been widely used in the field of solid-state batteries. Unlike liquid electrolytes, solid electrolytes do not have wettability. In the process of preparing the composite positive electrode, they need to be mixed with active materials and conductive agents to prepare a slurry, which makes the polymer electrolyte itself have a low ionic conductivity. Due to particle barriers, the connection between polymers is not tight, resulting in low ionic conductivity of the composite positive electrode, which in turn causes the battery to be charged and discharged only under low rate conditions. With the rapid development of battery performance, the demand for high energy density in polymer solid-state batteries is also increasing, which also means that the matching positive electrode load is getting higher and higher. In addition, the fluidity of polymer electrolytes is much lower than that of liquid electrolytes, resulting in obvious differences in the transmission of lithium ions in the composite positive electrode. When the thickness of the composite positive electrode is higher, the ionic conductivity close to the current collector side will be lower, which will seriously affect the rate performance and capacity of the battery.
[0029] Currently, there are two main methods to improve the ionic conductivity of positive electrode materials: one is to modify the positive electrode material by coating the surface of the active material with a material with high ionic conductivity or by doping doping atoms into the active material. However, the coating and doping process is complicated, and the coating and doping amounts are uncontrollable, which will lead to obvious differences in local ionic conductivity. The second is to optimize the formula by adjusting the composition and proportion of the positive electrode active material, solid electrolyte and conductive agent, thereby improving the diffusion mode of lithium ions inside it. However, this method has limited effect on the improvement of ionic conductivity.
[0030] In view of the above problems, the present application provides a solid-state battery positive electrode, which includes a current collector and a positive electrode active layer arranged on the current collector, the positive electrode active layer includes a positive electrode active material, a polymer additive and a conductive agent, and the positive electrode active layer includes at least two stacked active sublayers, and in any two adjacent active sublayers, the weight average molecular weight of the polymer additive in the active sublayer away from the current collector is greater than the weight average molecular weight of the polymer additive in the active sublayer close to the current collector. The solid-state battery positive electrode has a gradient ion conductivity in the thickness direction, which can improve the utilization rate of the active materials on the current collector side of the positive electrode and increase the capacity, while balancing the charge in the thickness direction of the pole piece and reducing polarization, optimizing the lithium ion transmission path and improving the battery rate performance. The present application also provides a method for preparing the solid-state battery positive electrode.
[0031] See also Figure 1 , the present application provides a solid-state battery positive electrode 100. Figure 1 As shown, the positive electrode 100 of the solid-state battery includes a current collector 101 and a positive electrode active layer 102 disposed on the current collector 101. The positive electrode active layer 102 includes a positive electrode active material, a polymer additive and a conductive agent. In an embodiment of the present application, the polymer additive includes one or more of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polytetrafluoroethylene, polyacrylonitrile, polypropylene carbonate, polyethylene oxide and ethylene oxide-propylene oxide copolymer. The positive electrode active layer 102 includes at least two stacked active sublayers, and in any two adjacent active sublayers, the weight average molecular weight of the polymer additive in the active sublayer away from the current collector 101 is greater than the weight average molecular weight of the polymer additive in the active sublayer close to the current collector 101.
[0032] In the embodiment of the present application, the positive electrode active layer 102 includes at least two stacked active sub-layers. Figure 2 As shown, the positive electrode active layer 102 includes three active sublayers stacked in a direction away from the current collector 101, namely, a first active sublayer 1021, a second active sublayer 1022, and a third active sublayer 1023, wherein the weight average molecular weight of the polymer additive in the first active sublayer 1021, the second active sublayer 1022, and the third active sublayer 1023 increases in sequence in a direction away from the current collector 101. The solid-state battery positive electrode 100 provided in this embodiment is taken as an example to further describe the solid-state battery positive electrode provided in the present application.
[0033] In the embodiment of the present application, in any two adjacent active sublayers, the weight average molecular weight of the polymer additive in the active sublayer on the side away from the current collector 101 is greater than the weight average molecular weight of the polymer additive in the active sublayer on the side close to the current collector 101. That is, in the adjacent first active sublayer 1021 and second active sublayer 1022, the weight average molecular weight of the polymer additive in the second active sublayer 1022 is greater than the weight average molecular weight of the polymer additive in the first active sublayer 1021; in the adjacent second active sublayer 1022 and third active sublayer 1023, the weight average molecular weight of the polymer additive in the third active sublayer 1023 is greater than the weight average molecular weight of the polymer additive in the second active sublayer 1022. The weight average molecular weight of the polymer additive in the first active sublayer 1021, the second active sublayer 1022, and the third active sublayer 1023 increases in sequence in the direction away from the current collector 101.
[0034] In the solid-state battery positive electrode 100, the weight average molecular weight of the polymer additive in the first active sublayer 1021 close to the current collector 101 is small, and the corresponding polymer additive chain length is short, with good fluidity, which can provide higher ion conductivity; the weight average molecular weight of the polymer additive in the third active sublayer 1023 away from the current collector 101 is large, and the corresponding polymer additive chain length is long, and the fluidity is poor, which can provide relatively excellent flexibility and adhesion, making the connection between the positive electrode and the solid electrolyte closer while reducing the probability of deformation cracks in the positive electrode during the cycle; the second active sublayer 1022 between the first active sublayer 1021 and the third active sublayer 1023 has a fluidity between the two, and has good ion conductivity and flexibility and adhesion. By arranging a positive electrode active layer 102 containing a polymer additive with a weight average molecular weight increasing in sequence on the current collector 101, a solid-state battery positive electrode 100 with gradient ion conductivity performance can be obtained. The structure of the gradient ion conductivity performance of the solid-state battery positive electrode 100 can effectively improve the utilization rate of the active material on the current collector side of the battery positive electrode and increase the capacity of the battery. In addition, the structure with gradient ion conductivity can balance the charge in the thickness direction of the composite positive electrode sheet and effectively reduce polarization, optimize the transmission path of lithium ions and improve the rate performance of the battery.
[0035] In the embodiment of the present application, the thickness of the current collector 101 is 8 μm-20 μm. In some embodiments, the thickness of the current collector 101 can be 8 μm, 9 μm, 10 μm, 12 μm, 13 μm, 15 μm, 16 μm, 18 μm, 19 μm, or 20 μm.
[0036] In an embodiment of the present application, the positive electrode active layer 102 includes at least two stacked active sublayers, and the thickness of each active sublayer is 50 μm-250 μm. In some embodiments, the number of active sublayers may be 2-4. In some embodiments, the number of active sublayers may be, for example, 2, 3, or 4. In some embodiments, the thickness of each active sublayer may be 50 μm, 80 μm, 100 μm, 120 μm, 130 μm, 150 μm, 170 μm, 180 μm, 200 μm, or 250 μm.
[0037] The thickness of the positive electrode active layer is related to the energy density of the battery. The thicker the positive electrode active layer, the more corresponding positive electrode active materials, the greater the energy density of the solid-state battery, and the larger the capacity, but the lower the ionic conductivity close to the current collector, the worse the rate performance of the battery; the thinner the positive electrode active layer, the less corresponding positive electrode active materials, the better the rate performance of the solid-state battery, but the lower the energy density, the smaller the capacity. For the active sublayer with a smaller weight average molecular weight of the polymer additive, controlling the thickness within a suitable range can ensure the fluidity of the active sublayer while giving it a certain adhesion, and avoid cracks inside the pole piece as much as possible, thereby increasing the polarization of the pole piece and reducing the capacity of the pole piece. For the active sublayer with a larger weight average molecular weight of the polymer additive, controlling the thickness within a suitable range can ensure the adhesion of the active sublayer while giving it a certain fluidity, and reduce the polarization of the battery as much as possible. Therefore, the present application controls the thickness and quantity of the active sublayer within a reasonable range and then controls the thickness of the positive electrode active layer, so as to better combine the solid-state battery positive electrode with relatively excellent rate performance and gradient ionic conductivity performance.
[0038] In the embodiment of the present application, the weight average molecular weight of the polymer additive is 10000 g / mol-1000000 g / mol. In some embodiments, the weight average molecular weight of the polymer additive can be 10000 g / mol, 50000 g / mol, 100000 g / mol, 300000 g / mol, 400000 g / mol, 500000 g / mol, 700000 g / mol, 800000 g / mol, 1000000 g / mol. The weight average molecular weight of the polymer additive in each active sublayer in the positive electrode active layer is related to the chain length of the polymer additive. The present application controls the weight average molecular weight of the polymer additive within a reasonable range, which can effectively alleviate the cracking problem caused by the short chain length of the polymer additive and the agglomeration problem caused by the long chain length of the polymer additive. In addition, usually when the weight average molecular weight of the polymer additive is small, the corresponding polymer additive chain length is also short, so that the active sublayer has better fluidity, can provide higher ion conductivity, reduce polarization, and thus improve the rate performance of the battery; when the weight average molecular weight of the polymer additive is large, the corresponding polymer additive chain length is also long, the fluidity of the active sublayer is poor, but it can provide the active sublayer with better flexibility and adhesion, making the connection between the positive electrode and the solid electrolyte tighter. By controlling the weight average molecular weight of the polymer additive in each active sublayer, when the weight average molecular weight of the polymer additive in the active sublayer increases in the direction away from the current collector, a solid-state battery positive electrode with gradient ion conductivity can be obtained.
[0039] In the embodiment of the present application, in any two adjacent active sublayers, the weight average molecular weight of the polymer additive in the active sublayer away from the current collector is greater than the weight average molecular weight of the polymer additive in the active sublayer close to the current collector by 100000 g / mol-600000 g / mol. In some embodiments, the weight average molecular weight of the polymer additive in the active sublayer away from the current collector is greater than the weight average molecular weight of the polymer additive in the active sublayer close to the current collector, which can be 100000 g / mol, 150000 g / mol, 200000 g / mol, 250000 g / mol, 300000 g / mol, 350000 g / mol, 400000 g / mol, 450000 g / mol, 500000 g / mol, 550000 g / mol, 600000 g / mol. The weight average molecular weight of the polymer additive can reflect the chain length of the polymer, that is, when the weight average molecular weight of the polymer is larger, the polymer chain length is longer; when the weight average molecular weight of the polymer is smaller, the polymer chain length is shorter. Controlling the difference in the weight average molecular weight of the polymer additive in any two adjacent active sublayers within an appropriate range can further make the positive electrode of the solid-state battery have a more obvious gradient ion conductivity in the thickness direction, thereby bringing better electrochemical performance to the battery, and avoiding as much as possible the small difference in ion conductivity caused by the large difference in weight average molecular weight, the insignificant improvement in rate performance, and the poor dispersion and mechanical properties of the pole piece caused by the small difference in weight average molecular weight.
[0040] In the embodiment of the present application, the positive electrode active layer 102 includes at least two stacked active sub-layers, and the types of polymer additives in each active sub-layer can be the same or different. Figure 2 As shown, the positive electrode active layer 102 includes three active sublayers stacked in a direction away from the current collector 101, namely, a first active sublayer 1021, a second active sublayer 1022, and a third active sublayer 1023. In some embodiments, the first active sublayer 1021, the second active sublayer 1022, and the third active sublayer 1023 can all be polyethylene oxide, for example. In other embodiments, the first active sublayer 1021 can be polyethylene oxide, the second active sublayer 1022 can be ethylene oxide-propylene oxide copolymer, and the third active sublayer 1023 can be polyacrylonitrile, for example.
[0041] In the embodiment of the present application, the positive electrode active material includes lithium cobalt oxide, lithium nickel oxide, lithium iron phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium nickel phosphate, lithium manganese oxide, LiNi x A (1-x) O2 and LiNi m E n M (1-m-n)O2, wherein A is selected from any one of Co and Mn, E and M are selected from any one of Co, Al and Mn, and E and M are different, 0 <x<1,0<m<1,0<n<1。
[0042] In an embodiment of the present application, the conductive agent includes one or more of acetylene black, Super P, Super S, graphene, carbon fiber, carbon nanotube and Ketjen black.
[0043] In the embodiment of the present application, the mass ratio of the positive electrode active material, the polymer additive, and the conductive agent in the positive electrode active layer is (50-90): (6-20): (1-10). In some embodiments, the mass ratio of the positive electrode active material, the polymer additive, and the conductive agent in the positive electrode active layer can be 70:20:10, 75:15:10, 80:10:10, 85:10:5, 90:9:1, 90:8:2, 90:6:4.
[0044] In the embodiment of the present application, the positive electrode active layer further includes a lithium salt and / or a plasticizer.
[0045] In an embodiment of the present application, the lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium dioxalatoborate, lithium difluorooxalatoborate and lithium tetrafluorooxalatophosphate.
[0046] In the embodiment of the present application, the plasticizer includes one or more of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol methyl ethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, 1,4-dioxane, succinonitrile and polyethylene glycol dimethyl ether having a weight average molecular weight of less than 1000.
[0047] In the embodiment of the present application, the current collector includes any one of aluminum foil, foamed aluminum, carbon-coated aluminum foil, carbon mesh, and carbon cloth.
[0048] The solid-state battery positive electrode provided by the present application includes a current collector and a positive electrode active layer disposed on the current collector, the positive electrode active layer includes a positive electrode active material, a polymer additive and a conductive agent, and the positive electrode active layer includes at least two stacked active sublayers, and in any two adjacent active sublayers, the weight average molecular weight of the polymer additive in the active sublayer away from the current collector is greater than the weight average molecular weight of the polymer additive in the active sublayer close to the current collector. The solid-state battery positive electrode has a gradient ion conductivity in the thickness direction, which can improve the utilization rate of the active material on the current collector side in the positive electrode and increase the capacity, while balancing the charge in the thickness direction of the pole piece and reducing polarization, optimizing the lithium ion transmission path and improving the battery rate performance.
[0049] The present application also provides a method for preparing a solid-state battery positive electrode, comprising:
[0050] Providing at least two composite positive electrode slurries, each of the composite positive electrode slurries comprises a positive electrode active material, a polymer additive and a conductive agent, and the polymer additives in the at least two composite positive electrode slurries have different weight average molecular weights;
[0051] By co-extrusion, the at least two composite positive electrode slurries are layered and coated on the surface of the current collector in the order of the weight average molecular weight of the polymer additives from low to high, so as to obtain a solid-state battery positive electrode precursor;
[0052] The solid-state battery positive electrode precursor is dried and rolled to obtain a solid-state battery positive electrode; the solid-state battery positive electrode includes a current collector and a positive electrode active layer arranged on the current collector, the positive electrode active layer includes at least two stacked active sublayers, and in any two adjacent active sublayers, the weight average molecular weight of the polymer additive in the active sublayer away from the current collector is greater than the weight average molecular weight of the polymer additive in the active sublayer close to the current collector.
[0053] In the embodiment of the present application, the composite positive electrode slurry is coated on the surface of the current collector by co-extrusion. The co-extrusion method can simplify the coating process, and multiple coatings are not required. Multiple active sub-layers can be coated once by co-extrusion.
[0054] In the embodiment of the present application, the composite positive electrode slurry containing polymer additives with different weight average molecular weights is used to prepare different active sublayers of the positive electrode active layer. During co-extrusion coating, the composite positive electrode slurry containing the polymer additive with a smaller weight average molecular weight is placed in the lower layer, and the composite positive electrode slurry containing the polymer additive with a larger weight average molecular weight is placed in the upper layer. After the solid-state battery positive electrode precursor is obtained, it is dried and rolled to obtain the solid-state battery positive electrode. The solid-state battery positive electrode includes a current collector and a positive electrode active layer arranged on the current collector, and the positive electrode active layer includes at least two stacked active sublayers. In any two adjacent active sublayers, the weight average molecular weight of the polymer additive in the active sublayer away from the current collector is greater than the weight average molecular weight of the polymer additive in the active sublayer close to the current collector. On the one hand, the co-extrusion method is simple and does not require multiple coatings; on the other hand, the composite positive electrode slurry containing a polymer additive with a smaller weight average molecular weight has a higher fluidity and lower adhesion. The co-extrusion coating can effectively avoid the cracking of the solid-state battery positive electrode during the baking process.
[0055] In the embodiment of the present application, the drying temperature of the positive electrode precursor of the solid-state battery is 60°C-120°C, and the drying time is 4h-16h. In some embodiments, the drying temperature of the positive electrode precursor of the solid-state battery can be 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, and the drying time can be 4h, 6h, 8h, 10h, 12h, 14h, 15h, 16h. The purpose of drying the positive electrode precursor of the solid-state battery after coating is to remove the solvent in the composite positive electrode slurry. After drying, rolling it can obtain a solid-state battery positive electrode with gradient ion conductivity.
[0056] The preparation method of the solid-state battery positive electrode provided in the present application adopts a co-extrusion method to coat a composite positive electrode slurry containing polymer additives with different weight average molecular weights to prepare a solid-state battery positive electrode with gradient ion conductivity. The preparation method is simple in process, does not require multiple coatings, and can effectively avoid cracking of the solid-state battery positive electrode during baking.
[0057] See also Figure 3 The present application also provides a solid-state battery 200. The solid-state battery 200 includes a positive electrode 201, a negative electrode 203, and a solid electrolyte 202 located between the positive electrode 201 and the negative electrode 203. The positive electrode 201 includes the solid-state battery positive electrode 100 provided above.
[0058] The present application also provides an electric device, which includes the solid-state battery 200 provided above. The electric device may be, for example, an electric car, a mobile phone, a tablet computer, a laptop computer, a wearable device (a watch, a bracelet), a digital camera, etc.
[0059] The present application is further described below in multiple embodiments:
[0060] Example 1
[0061] Lithium iron phosphate was selected as the active material, Super P as the conductive agent, polyethylene oxide as the polymer, lithium bis(trifluoromethanesulfonyl)imide as the lithium salt, and SN as the plasticizer, which were dissolved in N,N-dimethylformamide to form slurry A and slurry B. The weight average molecular weight of polyethylene oxide in slurry A is 30000 g / mol, and the weight average molecular weight of polyethylene oxide in slurry B is 700000 g / mol. In slurry A and slurry B, the mass ratio of positive electrode active material, conductive agent, polymer additive, lithium salt and plasticizer is 79:3:9:4.5:4.5. In terms of mass fractions, the number of positive electrode active materials in slurry A is 13 parts, and the number of positive electrode active materials in slurry B is 17 parts. Slurry A and slurry B are coated on the surface of the current collector together by co-extrusion coating, wherein slurry A is close to the current collector side and slurry B is close to the solid electrolyte side. The prepared solid-state battery positive electrode precursor was placed in a vacuum dryer at 80°C for 8 hours, and then rolled to obtain a solid-state battery positive electrode with gradient ion conductivity. The compaction density of the prepared solid-state battery positive electrode is 2.35g / cm 3 The thickness of the active sublayer A made from slurry A is 130 μm, and the thickness of the active sublayer B made from slurry B is 170 μm.
[0062] Example 2
[0063] Lithium iron phosphate was selected as the active material, Super P as the conductive agent, polyethylene oxide as the polymer, lithium bis(trifluoromethanesulfonyl)imide as the lithium salt, and SN as the plasticizer, which were dissolved in N,N-dimethylformamide to form slurry A and slurry B. The weight average molecular weight of polyethylene oxide in slurry A is 100000 g / mol, and the weight average molecular weight of polyethylene oxide in slurry B is 700000 g / mol. In slurry A and slurry B, the mass ratio of positive electrode active material, conductive agent, polymer additive, lithium salt and plasticizer is 79:3:9:4.5:4.5. In terms of mass fractions, the number of positive electrode active materials in slurry A is 13 parts, and the number of positive electrode active materials in slurry B is 17 parts. Slurry A and slurry B are coated on the surface of the current collector together by co-extrusion coating, wherein slurry A is close to the current collector side and slurry B is close to the solid electrolyte side. The prepared solid-state battery positive electrode precursor was placed in a vacuum dryer at 80°C for 8 hours, and then rolled to obtain a solid-state battery positive electrode with gradient ion conductivity. The compaction density of the prepared solid-state battery positive electrode is 2.35g / cm 3 The thickness of the active sublayer A made from slurry A is 130 μm, and the thickness of the active sublayer B made from slurry B is 170 μm.
[0064] Example 3
[0065] Lithium iron phosphate was selected as the active material, Super P as the conductive agent, polyethylene oxide as the polymer, lithium bis(trifluoromethanesulfonyl)imide as the lithium salt, and SN as the plasticizer, which were dissolved in N,N-dimethylformamide to form slurry A and slurry B. The weight average molecular weight of polyethylene oxide in slurry A is 300,000 g / mol, and the weight average molecular weight of polyethylene oxide in slurry B is 700,000 g / mol. In slurry A and slurry B, the mass ratio of positive electrode active material, conductive agent, polymer additive, lithium salt and plasticizer is 79:3:9:4.5:4.5. In terms of mass fractions, the number of positive electrode active materials in slurry A is 13 parts, and the number of positive electrode active materials in slurry B is 17 parts. Slurry A and slurry B are coated on the surface of the current collector together by co-extrusion coating, wherein slurry A is close to the current collector side and slurry B is close to the solid electrolyte side. The prepared solid-state battery positive electrode precursor was placed in a vacuum dryer at 80°C for 8 hours, and then rolled to obtain a solid-state battery positive electrode with gradient ion conductivity. The compaction density of the prepared solid-state battery positive electrode is 2.35g / cm 3 The thickness of the active sublayer A made from slurry A is 130 μm, and the thickness of the active sublayer B made from slurry B is 170 μm.
[0066] Example 4
[0067] Lithium iron phosphate is selected as the active material, Super P is the conductive agent, polyethylene oxide is the polymer, bis(trifluoromethanesulfonyl)imide lithium is the lithium salt, and SN is the plasticizer, which are dissolved in N,N-dimethylformamide to form slurry A and slurry B. The weight average molecular weight of polyethylene oxide in slurry A is 100000 g / mol, and the weight average molecular weight of polyethylene oxide in slurry B is 400000 g / mol. In slurry A and slurry B, the mass ratio of positive electrode active material, conductive agent, polymer additive, lithium salt and plasticizer is 79:3:9:4.5:4.5. In terms of mass fractions, the number of positive electrode active materials in slurry A is 13 parts, and the number of positive electrode active materials in slurry B is 17 parts. Slurry A and slurry B are coated on the surface of the current collector together by co-extrusion coating, wherein slurry A is close to the current collector side and slurry B is close to the solid electrolyte side. The prepared solid-state battery positive electrode precursor was placed in a vacuum dryer at 80°C for 8 hours, and then rolled to obtain a solid-state battery positive electrode with gradient ion conductivity. The compaction density of the prepared solid-state battery positive electrode is 2.35g / cm 3 The thickness of the active sublayer A made from slurry A is 130 μm, and the thickness of the active sublayer B made from slurry B is 170 μm.
[0068] Example 5
[0069] Lithium iron phosphate was selected as the active material, Super P as the conductive agent, polyethylene oxide as the polymer, lithium bis(trifluoromethanesulfonyl)imide as the lithium salt, and SN as the plasticizer, which were dissolved in N,N-dimethylformamide to form slurry A and slurry B. The weight average molecular weight of polyethylene oxide in slurry A is 100000 g / mol, and the weight average molecular weight of polyethylene oxide in slurry B is 1000000 g / mol. In slurry A and slurry B, the mass ratio of positive electrode active material, conductive agent, polymer additive, lithium salt and plasticizer is 79:3:9:4.5:4.5. In terms of mass fractions, the number of positive electrode active materials in slurry A is 13 parts, and the number of positive electrode active materials in slurry B is 17 parts. Slurry A and slurry B are coated on the surface of the current collector together by co-extrusion coating, wherein slurry A is close to the current collector side and slurry B is close to the solid electrolyte side. The prepared solid-state battery positive electrode precursor was placed in a vacuum dryer at 80°C for 8 hours, and then rolled to obtain a solid-state battery positive electrode with gradient ion conductivity. The compaction density of the prepared solid-state battery positive electrode is 2.35g / cm 3 The thickness of the active sublayer A made from slurry A is 130 μm, and the thickness of the active sublayer B made from slurry B is 170 μm.
[0070] Example 6
[0071] Lithium iron phosphate was selected as the active material, Super P as the conductive agent, polyethylene oxide as the polymer, lithium bis(trifluoromethanesulfonyl)imide as the lithium salt, and SN as the plasticizer, which were dissolved in N,N-dimethylformamide to prepare slurry A and slurry B. The weight average molecular weight of polyethylene oxide in slurry A was 100,000 g / mol, the weight average molecular weight of polyethylene oxide in slurry B was 300,000 g / mol, and the weight average molecular weight of polyethylene oxide in slurry C was 700,000 g / mol. In slurry A, slurry B, and slurry C, the mass ratio of positive active material, conductive agent, polymer additive, lithium salt, and plasticizer was 79:3:9:4.5:4.5. In terms of mass fractions, the number of positive active materials in slurry A was 10 parts, the number of positive active materials in slurry B was 6 parts, and the number of positive active materials in slurry B was 14 parts. The slurry A, slurry B and slurry C were coated on the surface of the current collector by co-extrusion coating. The slurry A, slurry B and slurry C were coated in the direction from the current collector to the solid electrolyte. The prepared solid-state battery positive electrode precursor was placed under vacuum drying at 80°C for 8 hours, and a solid-state battery positive electrode with gradient ion conductivity was obtained after roller pressing. The compacted density of the prepared solid-state battery positive electrode is 2.35g / cm 3 The thickness of the active sublayer A made from slurry A is 100 μm, the thickness of the active sublayer B made from slurry B is 60 μm, and the thickness of the active sublayer C made from slurry C is 140 μm.
[0072] Example 7
[0073] Lithium iron phosphate is selected as the active material, Super P is the conductive agent, polyethylene oxide is the polymer, lithium bis(trifluoromethanesulfonyl)imide is the lithium salt, and SN is the plasticizer, which are dissolved in N,N-dimethylformamide to form slurry A and slurry B. The weight average molecular weight of polyethylene oxide in slurry A is 100000 g / mol, and the weight average molecular weight of polyethylene oxide in slurry B is 700000 g / mol. In slurry A and slurry B, the mass ratio of positive electrode active material, conductive agent, polymer additive, lithium salt and plasticizer is 79:3:9:4.5:4.5. In terms of mass fractions, the number of positive electrode active materials in slurry A is 10 parts, and the number of positive electrode active materials in slurry B is 17 parts. Slurry A and slurry B are coated on the surface of the current collector together by co-extrusion coating, wherein slurry A is close to the current collector side and slurry B is close to the solid electrolyte side. The prepared solid-state battery positive electrode precursor was placed in a vacuum dryer at 80°C for 8 hours, and then rolled to obtain a solid-state battery positive electrode with gradient ion conductivity. The compaction density of the prepared solid-state battery positive electrode is 2.35g / cm 3 The thickness of the active sublayer A made from slurry A is 100 μm, and the thickness of the active sublayer B made from slurry B is 170 μm.
[0074] Example 8
[0075] Lithium iron phosphate is selected as the active material, Super P is the conductive agent, polyethylene oxide is the polymer, bis(trifluoromethanesulfonyl)imide lithium is the lithium salt, and SN is the plasticizer, which are dissolved in N,N-dimethylformamide to form slurry A and slurry B. The weight average molecular weight of polyethylene oxide in slurry A is 100000 g / mol, and the weight average molecular weight of polyethylene oxide in slurry B is 700000 g / mol. In slurry A and slurry B, the mass ratio of positive electrode active material, conductive agent, polymer additive, lithium salt and plasticizer is 79:3:9:4.5:4.5. In terms of mass fractions, the number of positive electrode active materials in slurry A is 13 parts, and the number of positive electrode active materials in slurry B is 12 parts. Slurry A and slurry B are coated on the surface of the current collector together by co-extrusion coating, wherein slurry A is close to the current collector side and slurry B is close to the solid electrolyte side. The prepared solid-state battery positive electrode precursor was placed in a vacuum dryer at 80°C for 8 hours, and then rolled to obtain a solid-state battery positive electrode with gradient ion conductivity. The compaction density of the prepared solid-state battery positive electrode is 2.35g / cm 3 The thickness of the active sublayer A made from slurry A is 130 μm, and the thickness of the active sublayer B made from slurry B is 120 μm.
[0076] Example 9
[0077] Lithium iron phosphate is selected as the active material, Super P is the conductive agent, polyethylene oxide is the polymer, lithium bis(trifluoromethanesulfonyl)imide is the lithium salt, and SN is the plasticizer, which are dissolved in N,N-dimethylformamide to form slurry A and slurry B. The weight average molecular weight of polyethylene oxide in slurry A is 100000 g / mol, and the weight average molecular weight of polyethylene oxide in slurry B is 700000 g / mol. In slurry A and slurry B, the mass ratio of positive electrode active material, conductive agent, polymer additive, lithium salt and plasticizer is 79:3:9:4.5:4.5. In terms of mass fractions, the number of positive electrode active materials in slurry A is 18 parts, and the number of positive electrode active materials in slurry B is 17 parts. Slurry A and slurry B are coated on the surface of the current collector together by co-extrusion coating, wherein slurry A is close to the current collector side and slurry B is close to the solid electrolyte side. The prepared solid-state battery positive electrode precursor was placed in a vacuum dryer at 80°C for 8 hours, and then rolled to obtain a solid-state battery positive electrode with gradient ion conductivity. The compaction density of the prepared solid-state battery positive electrode is 2.35g / cm 3 The thickness of the active sublayer A made from slurry A is 180 μm, and the thickness of the active sublayer B made from slurry B is 170 μm.
[0078] Example 10
[0079] Lithium iron phosphate is selected as the active material, Super P is the conductive agent, polyethylene oxide is the polymer, lithium bis(trifluoromethanesulfonyl)imide is the lithium salt, and SN is the plasticizer, which are dissolved in N,N-dimethylformamide to form slurry A and slurry B. The weight average molecular weight of polyethylene oxide in slurry A is 100000 g / mol, and the weight average molecular weight of polyethylene oxide in slurry B is 700000 g / mol. In slurry A and slurry B, the mass ratio of positive electrode active material, conductive agent, polymer additive, lithium salt and plasticizer is 79:3:9:4.5:4.5. In terms of mass fractions, the number of positive electrode active materials in slurry A is 13 parts, and the number of positive electrode active materials in slurry B is 25 parts. Slurry A and slurry B are coated on the surface of the current collector together by co-extrusion coating, wherein slurry A is close to the current collector side and slurry B is close to the solid electrolyte side. The prepared solid-state battery positive electrode precursor was placed in a vacuum dryer at 80°C for 8 hours, and then rolled to obtain a solid-state battery positive electrode with gradient ion conductivity. The compaction density of the prepared solid-state battery positive electrode is 2.35g / cm 3 The thickness of the active sublayer A made from slurry A is 130 μm, and the thickness of the active sublayer B made from slurry B is 250 μm.
[0080] Comparative Example 1
[0081] Lithium iron phosphate was selected as the active material, Super P as the conductive agent, polyethylene oxide as the polymer, lithium bis(trifluoromethanesulfonyl)imide as the lithium salt, and SN as the plasticizer, which were dissolved in N,N-dimethylformamide to form slurry A and slurry B. The weight average molecular weight of polyethylene oxide in slurry A is 700000 g / mol, and the weight average molecular weight of polyethylene oxide in slurry B is 700000 g / mol. In slurry A and slurry B, the mass ratio of positive electrode active material, conductive agent, polymer additive, lithium salt and plasticizer is 79:3:9:4.5:4.5, and the mass ratio of positive electrode active material in slurry A to positive electrode active material in slurry B is 13:17. Slurry A and slurry B are coated on the surface of the current collector by co-extrusion coating, with slurry A close to the current collector side and slurry B close to the solid electrolyte side. The prepared solid-state battery positive electrode precursor was placed in a vacuum dryer at 80°C for 8 hours, and then rolled to obtain a solid-state battery positive electrode with gradient ion conductivity. The compaction density of the prepared solid-state battery positive electrode is 2.35g / cm 3 , the thickness of the positive electrode active layer is 300μm.
[0082] The solid-state battery positive electrodes prepared in Examples 1-10 and Comparative Example 1 were subjected to ion conductivity tests at 60°C. The solid-state battery positive electrodes prepared in Examples 1-10 and Comparative Example 1 were used as positive electrodes, polyethylene oxide was used as polymer electrolyte, lithium bistrifluoromethanesulfonyl imide was used as lithium salt, acetonitrile was used as plasticizer, and metallic lithium was used as negative electrode to assemble into soft-pack batteries and conduct overpotential tests at 60°C. The measured results are shown in Table 1.
[0083] Table 1 Electrochemical properties of solid-state battery positive electrodes prepared in Examples 1-10 and Comparative Example 1 and assembled soft-pack batteries thereof
[0084]
[0085] From the comparison between Comparative Example 1 and Examples 1-10, it can be seen that Examples 1-10 control the weight average molecular weight of the polymer additive in the composite positive electrode slurry, thereby regulating the chain length of the polymer additive, so as to achieve the preparation of a solid-state battery positive electrode with gradient ion conductivity. Compared with the positive electrode sample without gradient ion conductivity in Comparative Example 1, under the same conditions, the solid-state battery positive electrode has a greater ion conductivity and a lower overpotential of the prepared battery. Therefore, the solid-state battery positive electrode with gradient ion conductivity provided in the present application can effectively improve ion conductivity, reduce polarization, and thus improve the rate performance of the battery.
[0086] As can be seen from Examples 1-6, the weight average molecular weight of the polymer additive, that is, the chain length of the polymer additive, has an important influence on the performance of the positive electrode of the solid-state battery. When the weight average molecular weight of the polymer additive is too large, the chain length of the polymer is too long, the degree of segment motion decreases, and the lithium ion transmission speed slows down; when the weight average molecular weight of the polymer additive is too small, the polymer chain length is too short, the adhesion between the slurry and the current collector is insufficient, and cracking is easily generated, resulting in a decrease in ionic conductivity. Therefore, in order to make the positive electrode have better electrochemical properties, the present application controls the weight average molecular weight of the polymer additive within a suitable range. And it can be seen from Examples 2 and 6 that when the difference in the weight average molecular weight of the polymer additive between the active sublayer with the smallest weight average molecular weight of the polymer additive in the positive electrode active layer and the active sublayer with the largest weight average molecular weight of the polymer additive is the same, increasing the number of active sublayers can further increase the effect of gradient ion conductivity, thereby further improving the electrochemical performance of the battery.
[0087] It can be seen from Examples 7-10 that reducing the thickness of each active sublayer can obtain better rate performance, but at the same time it will reduce the energy density of the electrode; increasing the thickness of each active sublayer will increase the energy density of the electrode but increase polarization and reduce the rate performance of the battery. Therefore, the present application controls the thickness of the active sublayer within a suitable range, which can further comprehensively improve the electrochemical performance of the positive electrode.
[0088] The preferred embodiments are described in detail above, but the present invention is not limited to the above-mentioned specific implementation modes. Under the guidance of the present application, technicians in this field can also make various specific changes without departing from the scope of protection of the present application, which all fall within the scope of protection of the present invention.
Claims
1. A solid-state battery positive electrode, characterized in that: The positive electrode of the solid-state battery includes a current collector and a positive electrode active layer arranged on the current collector, the positive electrode active layer includes a positive electrode active material, a polymer additive and a conductive agent, the polymer additive includes one or more of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polytetrafluoroethylene, polyacrylonitrile, polypropylene carbonate, polyethylene oxide and ethylene oxide-propylene oxide copolymer; the positive electrode active layer includes at least two stacked active sublayers, and in any two adjacent active sublayers, the weight average molecular weight of the polymer additive in the active sublayer away from the current collector is greater than the weight average molecular weight of the polymer additive in the active sublayer close to the current collector.
2. The solid-state battery positive electrode according to claim 1, characterized in that The thickness of the current collector is 8 μm-20 μm, and the thickness of the active sublayer is 50 μm-250 μm.
3. The solid-state battery positive electrode according to any one of claims 1 or 2, characterized in that: The weight average molecular weight of the polymer additive is 10000 g / mol-1000000 g / mol.
4. The solid-state battery positive electrode according to any one of claims 1 to 3, characterized in that: In any two adjacent active sublayers, the weight average molecular weight of the polymer additive in the active sublayer away from the current collector is 100,000 g / mol-600,000 g / mol greater than the weight average molecular weight of the polymer additive in the active sublayer close to the current collector.
5. The solid-state battery positive electrode according to any one of claims 1 to 4, characterized in that: The mass ratio of the positive electrode active material, the polymer additive and the conductive agent in the positive electrode active layer is (50-90): (6-20): (1-10).
6. The solid-state battery positive electrode according to any one of claims 1 to 5, characterized in that: The positive electrode active material includes one or more of lithium cobaltate, lithium nickelate, lithium iron phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium nickel phosphate, lithium manganate, LiNi x A (1-x) O2 and LiNi m E n M (1-m-n) O2, wherein A is selected from any one of Co and Mn, E and M are each selected from any one of Co, Al, and Mn, and E and M are different, 0 < x < 1, 0 < m < 1, 0 < n < 1; the conductive agent includes one or more of acetylene black, Super P, Super S, graphene, carbon fiber, carbon nanotube, and Ketjen black.
7. The solid-state battery positive electrode according to any one of claims 1 to 6, characterized in that: The positive electrode active layer also includes a lithium salt and / or a plasticizer; the lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium dioxalate borate, lithium difluorooxalate borate and lithium tetrafluorooxalate phosphate; the plasticizer includes one or more of N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, ethylene glycol methyl ethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, 1,4-dioxane, succinonitrile and polyethylene glycol dimethyl ether with a weight average molecular weight of less than 1000.
8. A method for preparing a solid-state battery positive electrode, characterized in that: include: Providing at least two composite positive electrode slurries, each of the composite positive electrode slurries comprises a positive electrode active material, a polymer additive and a conductive agent, and the polymer additives in the at least two composite positive electrode slurries have different weight average molecular weights; By co-extrusion, the at least two composite positive electrode slurries are layered and coated on the surface of the current collector in the order of the weight average molecular weight of the polymer additives from low to high, so as to obtain a solid-state battery positive electrode precursor; The solid-state battery positive electrode precursor is dried and rolled to obtain a solid-state battery positive electrode; the solid-state battery positive electrode includes a current collector and a positive electrode active layer arranged on the current collector, the positive electrode active layer includes at least two stacked active sublayers, and in any two adjacent active sublayers, the weight average molecular weight of the polymer additive in the active sublayer away from the current collector is greater than the weight average molecular weight of the polymer additive in the active sublayer close to the current collector.
9. A solid-state battery, characterized in that: The battery comprises a positive electrode, a negative electrode and a solid electrolyte located between the positive electrode and the negative electrode, and the positive electrode comprises the solid-state battery positive electrode according to any one of claims 1 to 7.
10. An electrical device, characterized in that: The electrical device comprises the solid battery as claimed in claim 9.
Citation Information
Patent Citations
Fixed electrolyte and lithium-based battery using the same
CN103165936A
Positive plate, solid electrolyte and preparation method of battery
CN116666550A
Cited By
Positive plate and preparation method thereof, battery, battery pack and electric equipment
CN120261547A